Sclerostin as a new target of diabetes-induced osteoporosis - Li, Yanhua; Luo, Yaheng; Huang, Debin; Peng, Lele (Frontiers in Endocrinology, 2024)
Sclerostin, a protein synthesized by bone cells, is a product of the SOST gene. Sclerostin is a potent soluble inhibitor of the WNT signaling pathway, and is known to inhibit bone formation by inhibiting osteocyte differentiation and function. Currently, sclerostin has been the subject of numerous animal experiments and clinical investigations. By conducting a literature review, we have gained insights into the most recent advancements in research. Patients with both type 1 diabetes and type 2 diabetes have high levels of serum sclerostin. Patients with type 1 diabetes and type 2 diabetes are both more likely to suffer from osteoporosis, and serum sclerostin levels are elevated in osteoporosis. Many studies have confirmed that sclerostin has been implicated in the pathogenesis of osteoporosis, so we speculate that sclerostin plays an important role in osteoporosis through the glucose metabolism pathway, which may promote the osteoporosis of morbidity in type 1 diabetes and type 2 diabetes.Based on this, we propose whether serum sclerostin can predict type 1 diabetes and type 2 diabetes-induced osteoporosis, and whether it can be a new target for the prevention and treatment of type 1 diabetes and type 2 diabetes-induced osteoporosis, providing new ideas for clinicians and researchers.